Inclusive Education Learning Model for Students with Learning Difficulties - Abidin, Zaenal; Kuswanto, Kuswanto; Nurdianingsih, Fitri (CV. Zabags Qu Publish, 2023)
This study aims to obtain data about a learning model specifically designed for children who experience learning difficulties at Tanjung Jabung Timur Public Elementary School. The research was carried out using the Research and Development method with a qualitative approach with descriptive analysis (observation and documentary studies). The population is an elementary school providing inclusive education in East Tanjung Jabung, with a sample size of 11 schools; the sampling technique used is random sampling. The research instrument used a questionnaire. The results are: 1) Not a single school uses a special learning model for children with learning difficulties, and 2) The learning model used still uses conventional learning models where children are treated the same as normal children (no learning difficulties).